Impact of the impulse electrophoresis of the blood plasma on the wounds healing and formation of cicatricial tissue in experiment - G. V. Terehov; M. V. Chukhraiev; M. V. Kostyliev; S. P. Galych; O. Yu. Furmanov; I. M. Savytska; O. A. Geylenko (Клінічна хірургія, 2019)
Objective. To study in experiment the impact of the impulse electrophoresis of the blood plasma method on the wounds healing process in postoperative wounds.